START-UP DIGITAL: TRANSFORMATION OF LOCAL ECONOMIC BEHAVIOR IN GLOBAL WORLD - Antari, Ni Nyoman Wulan; Wulandari, Riza (Journal of Research in Business, Economics, and Education, 2019)
The digital world brings a great influence for the actions of economic practitioners. This research will try to describe the startup phenomenon as a form of transformation of the actions of economic practitioners in the global world. The selection of the research objects and subjects is on ITB STIKOM Bali Campus with tenant (startup) informants who are starting a business and are given facilities in the form of incubators by the academics who are competent in their fields. Data collection techniques are carried out using interviews and documentation. The results of this study indicate that four digital startup tenants are under the shelter of the STIKOM Bali Business Incubator, they are Pasupati.id, Troll, Jemari Channel, and Agrito. ITB Stikom Bali is one of the leading universities in the field of technology by not leaving the roots of Indonesian culture, especially Balinese culture, with the contribution of Pasupati.id startups, digital homes for Balinese artists and the Jemari Channel is a digital commodity space for Bali endek craftsmen. The four startups transformed from conventional sales to digitalization.